Wajit Cililin Packaging Design Innovation Using the Product-Market Fit Approach and Value Proposition Canvas: Case Study Legieta Boga Priangan - Haibatuzahra, Aviefah; Ratnaningtyas, Sudrajati (Integrasi Sains Media, 2025)
This research is precipitated by two critical exigencies: the burgeoning scarcity of corn leaves as a primary packaging medium and the diminishing competitiveness of traditional products in contemporary markets due to suboptimal packaging aesthetics. The study investigates packaging design innovation at Legieta Boga Priangan, a Micro, Small, and Medium Enterprise (MSME) specializing in Wajit Cililin, aiming to enhance product-market alignment while preserving cultural identity by integrating the Product-Market Fit and Value Proposition Canvas frameworks. Employing a qualitative exploratory methodology involving 13 respondents, data were gathered via in-depth interviews to systematically map